Penerapan Model Pembelajaran Problem Based Learning Untuk Meningkatkan Minat Belajar Siswa Pada Mata Pelajaran Bahasa Inggris di SMP Islam Al Amin Cikarang Utara Kabupaten Bekasi - Yuny Sya’bani Rahmatilah (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
This research was conducted as a response to students' low interest in learning in English subjects at Al Amin Islamic Middle School, North Cikarang, Bekasi Regency. Several factors that cause this low interest include the lack of attractiveness of the material, monotonous teaching methods, and the lack of connection between English language material and students' daily lives. The impact is a decrease in students' interest in these subjects, which can affect their interest in learning. In an effort to increase students' interest in learning, the Problem Based Learning (PBL) learning model is used, where the teacher gives students ample opportunities to determine problem topics that are relevant to the learning material, even though the teacher has prepared the material that will be discussed in the lesson. The learning process is focused on students' abilities to solve problems systematically and logistically. This research uses a qualitative approach with descriptive methods. Through observation, interviews and documentation, the research results show that the application of the PBL learning model at Al Amin Islamic Middle School, North Cikarang, Bekasi Regency can increase students' interest in learning. English teachers who use the PBL model get good responses from students, where students are active in the teaching and learning process, ask questions actively, and are able to answer questions well and appropriately during discussions. The PBL learning model also encourages students to be more diligent in doing their assignments and provides high motivation to learn. Students find it easier to solve problems and are able to apply the knowledge they have.